The bio-physics of marine larval dispersal - Sammarco, Paul W.; Heron, Mal L. (Washington, D.C. American Geophysical Union., 1994)
Coastal and estuarine studies; 45
Keywords: Biophysics; Marine fishes; Marine invertebrates